Performance-Based Feedback to Enhance Preservice Teachers' Practice and Preschool Children's Expressive Communication. (March 2020) - Coogle, Christan Grygas; Ottley, Jennifer R.; Storie, Sloan; Rahn, Naomi L.; Kurowski-Burt, Amy
A multiple-probe, single-case design was used to determine the effect of delayed and immediate performance-based feedback on preservice teachers' use of embedded learning opportunities, an evidence-based practice in early childhood special education, as well as focus children's expressive communication and responses to preservice teachers' practice. Results suggest delayed performance-based feedback improved preservice teachers' practice, which was further enhanced when immediate feedback was used. Positive outcomes were observed across children for both their responses and overall expressive communication.